A Method of Model Experiments for Regularizing the Problem of Recovery of the Input Signal of the Linear Object by the Integral Dynamic Model - Sterten, Jo; Furtat, Yu.O. (Математичне та комп'ютерне моделювання. Серія: Технічні науки, 2017)
The method of determining the parameter of regularization for solving the problem of restoring the input signal of a linear stationary object under the conditions of the existence of measurement errors and the process of solving is considered. The proposed method of model experiments allows to separate errors of different types and restore the real input signal. Розглядається спосіб визначення параметру регуляризації для розв’язання задачі відновлення вхідного сигналу лінійного стаціонарного об’єкту в умовах існування похибок вимірювання та процесу розв’язування. Запропонований метод модельних експериментів дозволяє відокремлювати похибки різних типів і відновлювати справжній вхідний сигнал.